Ineficacia de la acción de repetición - Guillermo Enríquez Burbano (Ius Humani. Jornal do direito, 2017)
This research includes the study of the action of repetition, within the art. 11.9 of the Constitution of the Republic of Ecuador, it is noteworthy that the supreme law embodies the principle or right of the State to compensation for damage caused by servers public whose actions marked by intent or fraud have caused it. the absence of a specific and effective procedure through which the action of repetition, consequently achieving the corresponding executable statement is demanded, a situation that calls to approach new elements to the present process is verified. The current regulation of the action of repetition ensures that judges who know the causes can not rule on intent or gross negligence of officials or public servants, and the degree of responsibility for them, hence it is necessary to achieve effective determination responsible so he can answer for the compensation amounts derived from the domestic and international decisions when Ecuador must assume them, such a situation results in an economic loss to the exchequer and a perpetuation of impunity for the actions carried out irresponsibly by officials or public servants that may affect third.